Răspuns :
X+y=5
X=5-y
E=(x-y)^2-2xy+3(-x-y)+4xy+6
E=[(5-y)-y]^2-2(5-y)y+3[(-5+y)-y]+4(5-y)y+6
E=(5-y-y)^2-(10-2y)y+3(-5+y-y)+(20-4y)y+6
E=(5-2y)^2-10y-2y^2-15+20y-4y^2+6
E=5^2-2•5•2y+(2y)^2-10y-2y^2-15+20y-4y^2+6
E=25-10y+4y^2-10y-15+20y-4y^2+6
E=25-20y+20y+4y^2-4y^2-15+6
E=25-15+6
E=10+6
E=16
X=5-y
E=(x-y)^2-2xy+3(-x-y)+4xy+6
E=[(5-y)-y]^2-2(5-y)y+3[(-5+y)-y]+4(5-y)y+6
E=(5-y-y)^2-(10-2y)y+3(-5+y-y)+(20-4y)y+6
E=(5-2y)^2-10y-2y^2-15+20y-4y^2+6
E=5^2-2•5•2y+(2y)^2-10y-2y^2-15+20y-4y^2+6
E=25-10y+4y^2-10y-15+20y-4y^2+6
E=25-20y+20y+4y^2-4y^2-15+6
E=25-15+6
E=10+6
E=16